National situation, trends, and predictions of disease burden of atopic dermatitis in Chinese children and adolescents - Guo, Yang; Zhang, Kao-Yuan; Zou, Yan-Fen; Yu, Bo (Frontiers in Microbiology, 2023)
Background: Atopic dermatitis (AD) is an important global health problem affecting children and adolescents and detailed national information of disease burden in China is lacking. We aimed to evaluate the national disease burden of AD in Chinese children and adolescent, to provide the temporal trends over the past 30 years and to predict the burden for the next 10 years. Methods: The data of AD in China, including incidence, prevalence, and DALY, and population data were obtained from the Global Burden of Disease Study 2019 (GBD study 2019), which were estimated using the DisMod-MR 2.1. We analyzed the three measures by age and sex; the age groups were <5 years, 5-9 years, 10-14 years, and 15-19 years. The joinpoint regression analyses was conducted to assess the temporal trends from 1990 to 2019. The Bayesian age-period cohort (BAPC) model was used to predict measures from 2020 to 2030. Results: In 2019, the highest incidence case and rate were observed in <5 years group; for prevalence and disability adjusted life year (DALY), the groups of <5 years and 5-9 years showed similar higher levels and the groups of 10-14 years and 15-19 years had similar relatively lower levels. Overall, the male-to-female ratios were >1 in < 5 years group and <1 in 10-14 and 15-19 age groups. The trend analyses found an overall trend of decrease in cases of the three measures; in recent about three years, slight increase trends were shown in cases and rates of the three measures in <5 years group. The prediction analyses found a slight decreasing trend for cases of these measures and a slight increasing trend for rates of these measures in the <5 years group in the next 10 years; the 5-9 years group was predicted to increase slightly in rates of the three measures. Conclusion: In conclusion, the groups of < 5 years and 5-9 years are two important populations that need targeted measures to reduce disease burden of AD in China. Regarding sex disparity, we should pay more attention to males in < 5 years group and to females in 10-19 years group.